Corrupción a nivel local en Brasil: ¿la descentralización como un obstáculo? - Melo Aranha, Ana Luiza (Pontificia Universidad Católica del Perú, 2015)
Recently, Brazil has undergone decentralization processes that could have strengthened the local level in democratic terms. Notwithstanding, the results of these processes were not con-sensual, and corruption persisted as a feature of the Brazilian local level.This paper focuses on the corrupt conduct of municipal public officials who deal with fe- deral funds transferred by the central government. The information collected is part of a profile of corruption in the cities monitored by the federal Executive, revealing both how this phenomenon is distributed in terms of areas and which possible factors can explain the occurrence of corrup- tion in the Brazilian local governments. This paper deals with corruption in the municipalities of Minas Gerais - one of the 26 Brazilian states - from a conception of corruption as the misuse offunds by the political system.The argument focuses on the conduct of municipal public officials who deal with federalfunds transferred to Minas Gerais´ municipalities. In order to conduct this study, we used the reports from the Program of Inspections from Public Lotteries produced by the Office of the Comp- troller General (CGU). First, we built a general profile of the situation in those cities surveyed by the CGU regarding the incidence of irregularities. By doing so, we highlighted which gover- nmental areas would be in a more critical situation. These irregularities, in turn, were taken as proxies for the occurrence of corruption in two different ways. In the first place, according to the amount of irregularities found – which included all kind of irregularities, from formal mistakes to overbilling –, statistical tests were performed in order to establish which factors could be taken as constraints of corruption at the local level. We identified political, social, economic and demo- graphic characteristics that were associated with corruption, in its petty form. On the other hand, we also categorized corruption in a more strict way, considering only the cases in which larger amounts of resources were involved and leaving out the formal irregularities.We demonstrated that not all factors related with corruption in its broader sense (population size, the characteristic of the transfers, municipal characteristics related to income, education and control) kept significantly associated with the incidence of more severe irregularities. We seek to contribute to the debate about whether or not the local level is more susceptible to corruption, which means discussing if decentralization can be understood as a pitfall.

Recientemente, Brasil ha experimentado procesos de descentralización que podrían haber fortalecido el nivel local en términos democráticos. No obstante, los resultados de estos procesos no han sido consensuados y la corrupción ha persistido como una característica del nivel local en este país.El presente artículo se centra en la conducta corrupta de autoridades municipales que se ocupan de los fondos federales transferidos por el gobierno central. La información obtenida forma parte del perfil de corrupción en ciudades supervisadas por el Poder Ejecutivo federal. Asi- mismo, revela cómo este fenómeno se distribuye en función de las áreas gubernamentales y qué posibles factores pueden explicar la presencia de corrupción en los gobiernos locales brasileños.Este artículo se ocupa de la corrupción, entendida como el mal uso de fondos por parte del sistema político, en las municipalidades de Minas Gerais, uno de los 26 estados de Brasil. El argumento se centra en la conducta de las autoridades municipales que se encargan de los fondos federales. Para llevar a cabo este estudio, se utilizaron los informes del Programa de Inspecciones por Sorteos Públicos elaborados por la Oficina de Contraloría General (CGU). En primer lugar, se construyó un perfil general de la situación de las ciudades encuestadas por la CGU en relación a la incidencia de irregularidades. Al hacerlo, se destacaron las áreas gubernamentales que estarían en una situación más crítica. Estas irregularidades, a su vez, fueron tomadas como indicadores indirectos de incidencia de la corrupción de dos maneras diferentes. Por un lado, de acuerdo a la cantidad de irregularidades encontradas –que incluían todo tipo de irregularidades, desde errores formales hasta sobrefacturación– se aplicaron pruebas estadísticas con el fin de establecer qué factores podían ser tomados como limitaciones de la corrupción a nivel local. Se identificaron características políticas, sociales, económicas y demográficas, asociadas con la corrupción. Por otro lado, se definió la corrupción de una manera más estricta, tomando en cuenta solo los casos que involucraban grandes cantidades de recursos y se dejó de lado las irregularidades formales. Se demostró que no todos los factores relacionados con la corrupción en su sentido más amplio (tamaño de la población, características de las transferencias, características municipales relacionadas con los ingresos, educación y control) se mantienen significativamente asociados a la incidencia de irregularidades más graves. Se busca así contribuir al debate sobre si el nivel local es más susceptible o no a la corrupción, lo cual significa discutir también si la descentralización puede ser entendida como un obstáculo.
Corruption at the local level in Brazil: decentralization as a pitfall?
Keywords: Politics; Decentralization; Corruption; Local Government; Public Administration; Brazil; Descentralización; Corrupción; Gobierno Local; Administración Pública; Brasil; https://purl.org/pe-repo/ocde/ford#5.06.00